HadGEM3-GC31-MM year-long ENSO, QBO, and sea-ice simulations - Smith, Doug; Eade, Rosie; Walsh, Amber (Zenodo, 2022)
HadGEM3-GC31-MM year-long (June to May) simulations of two ENSO,two QBO, and two sea-ice states. The ENSO states are neutral ENSO and El Niño, the QBO states are QBO westerly and easterly, and the sea-ice states are present day and future sea-ice (following the PAMIP protocol ). There are 150 ensemble members per experiment. HadGEM3 is run in an atmosphere only configuration. The variables making up this dataset are zonalwind (ua), sea level pressure (psl), vertical Eliassen-Palm flux (epfz), and Eliassen-Palm flux divergence (epfd). Zonal means are givenfor ua, epfz, and epfd. This data is uploaded to support the paper "Nonlinear response of the extratropics to tropical climate variability" submitted to Geophysical Research Letters.